The racial saving gap enigma: unraveling the role of institutions - Willie Belton; Ruth Uwaifo Oyelere (Institute for the Study of Labor (IZA), 2008)
It has been well documented in the literature that ethnicity matters significantly in the determination of savings. In particular, African-American savings lag far behind savings for other ethnic groups. Similarly, the literature also provides evidence of the long-lived nature of institutions and the link between institutions and culture. In this paper, we provide an explanation for the savings gap that still exists between African-Americans and White Americans even after accounting for appropriate factors that can lead to savings differentials. We initially provide evidence that the savings gap exists and persist after including several control variables in a regression analysis. We then provide evidence that the persistent gap can not be attributed solely to racial discrimination but can be explained by the response of culture to institutional scaffolding erected many years earlier. Using a novel within race decomposition we provide evidence that past institutions transmitted through culture can help to explain this persistent saving disparity.
urn:nbn:de:101:1-20080619213
Keywords: D14; 300; Savings gap; institutions; race; culture; Sparen; Ethnische Gruppe; Wirtschaftsethnologie; Schwarze; Ethnische Diskriminierung; Institutionalismus; USA